THE LEGAL PROTECTION OF REFUGEE: WESTERN BALKANS - Elena ANDREEVSKA (Challenges of the Knowledge Society)
States have been granting protection to individuals and groups fleeing persecution for centuries; however, the modern refugee regime is largely the product of the second half of the twentieth century. Like international human rights law, modern refugee law has its origins in the aftermath of World War II as well as the refugee crises of the interwar years that preceded it. The refugee in international law occupies a large space characterized, on the one hand, by the principle of State sovereignty and, on the other hand, by competing humanitarian principles deriving from general international law and from treaty. The study of refugee protections invites a look not only at States’ obligations with regard to admission and treatment after entry, but also at the potential responsibility in international law of the State whose conduct or omissions cause an outflow. The community of nations is responsible in a general sense for finding solutions and in providing international protection to refugee. This special mandate was entrusted to UNHCR. At the start of the 21st century, protecting refugees means maintaining solidarity with the world’s most threatened, while finding answers to the challenges confronting the international system that was created to do just that. The aim of this article is to describe the foundations and the framework of international refugee law, to define refugees and protection of refugees; as well as to provides a brief analysis of the changing migration and asylum dynamics in the region and outlines some of the main challenges arising in this context..